COMPARABLE LEARNING OF WORD ORDER IN DIFFERENT LANGUAGES - Khidirova Nilufar Abdiaxatovna (American Journals, 2023)
In different languages word order can be different, especially if they are not closely related to each other. Every language has own peculiarities making up sentence. So some languages can be seen more distinctive features rather than similarities. However, morphological side of three languages can be found the change of the verb and omission of the subject.
Keywords: Typical word order, untypical word order, affirmative sentence, interrogative sentence, imperative sentence, special question, general question.